Evaluation of Gold Content in Coruh Placer Deposits - Gungor, Yildirim; Kursun, Ilgin (Asian Journal of Chemistry, 2016)
The aim of this study is the investigation of the Coruh region's geological and minerals engineering properties, especially gold content.